The shell morphology of the latest Cretaceous (Maastrichtian) trionychid turtle Helopanoplia distincta - Walter G. Joyce; Tyler R. Lyson (PeerJ, 2017)
Background Helopanoplia distincta is an extinct soft-shelled turtle (Pan-Trionychidae) for which the type specimen is a fragmentary costal and the inguinal notch portion of the left hypoplastron from the Late Cretaceous (Maastrichtian) Lance Formation of Wyoming, USA that bear a distinct surface sculpture pattern consisting of raised tubercles. Over the course of the past few decades, a number of additional, fragmentary specimens from the Late Cretaceous (Maastrichtian) Hell Creek Formation of Montana and North Dakota have been referred to this taxon based on the presence of these tubercles, but a more complete understanding of the anatomy and phylogenetic relationships of this distinctive soft-shelled turtle is still outstanding. Methods We here figure and describe shell remains of eight fossils referable to Helopanoplia distincta from the Hell Creek Formation of Montana and North Dakota that, in combination, document nearly all aspects of the shell morphology of this taxon. We furthermore explore the relationships of this fossil turtle by inserting it into a modified phylogenetic analysis of pan-trionychid relationships. Results The new fossil material thoroughly supports the validity of Helopanoplia distincta. In addition to its unique surface sculpture pattern, this turtle can be diagnosed relative to all other named pan-trionychids by the presence of a distinct corner along the margin of costals II, the complete covering of costal ribs I–VI by metaplastic bone, midline contact of the main plastral elements, hyoplastral shoulder, presence of a lateral, upturned margin on the hyo/hypoplastron that is covered dorsally and laterally by sculptured metaplastic bone, a single, lateral hyoplastral process, and the apomorphic presence of fine scallops along the margin of costals VIII, formation of a laterally embraced, rounded nuchal, anteriorly rounded costals I, distally expanded costals II, and narrow costals VII. A phylogenetic analysis places Helopanoplia distincta as sister to the clade formed by Plastomenus thomasii and Hutchemys spp., thereby confirming its identity as a plastomenid. The vast majority of Helopanoplia distincta material has been recovered from fine-grained overbank deposits, thereby supporting the hypothesis that this turtle favored ponded waters.